Effect of Precursor on the Mineralogy and Microstructure Characteristic of Nano Zirconia by Template Method - Naili Sofiyaningsih; Suhanda Suhanda; Rifki Septawendar (Jurnal Keramik dan Gelas Indonesia, 2020)
Nano zirconia     were successfully synthesized from Zr(OH)4 dan ZrOCl2 using a template method. Polyvinyl alcohol was added as a template or a surfactant to control the particle size of nano zirconia. Zirconia precursors were reacted with polyvinil alcohol at a stoichiometric and nonstoichiometric ratio in water solvent at about pH 4 and then calcined at a temperature of 800⁰C. The result showed the precursor types obviously affected the mineralogy and microstructure characteristics of nano zirconia.  The reaction between Zr(OH)4 and polyvinyl alcohol produces tetragonal zirconia in the form of nanorods with a diameter of 100 nm and 500 nm - 1μm in length, and elongated agglomerates consisting of nanoparticles less than 100 nm in sizes. Meanwhile, the reaction between ZrOCl2 precursor with polivinyl alcohol at pH 4 leaded to formation of monoclinic zirconia with microstructures such as nanorods with diameter of 10~100 nm and 100~500 nm in length, agglomeration of nanoparticles <100 nm, and  packing sheets.